Seta length variation and the refutation of Hedwigidium=Braunia (Hedwigiaceae, Bryopsida) - de Luna, Efraín (Instituto de Ecología, A.C., 2021)
Background and Aims: Traditionally regarded as a monotypic genus, Hedwigidium was recently proposed to be identical to Braunia, because “… some Braunia species have a seta as short as that of Hedwigidium”. This paper offers data and analyses for a refutation of the taxonomic hypothesis that Hedwigidium=Braunia. Methods: Seta length measurements (n=682) were sampled in 20 species of the four genera of Hedwigiaceae to compare variation between Hedwigia (n=10), Hedwigidium (n=40), Braunia (n=614), and Pseudobraunia (n=18). Measurements were subjected to analyses of variance and multiple comparison tests, to reveal if some Braunia species have a seta as short as that of Hedwigidium, or not. Key results: Analyses of variance followed by Mann-Whitney pairwise tests reveal that the average seta length in Hedwigidium imberbe (0.7 mm, sd=0.21) is different from the average seta length in each of the seven Braunia species with short setae, all in the range of 2.0-2.3 mm. For the first time, the geographical distribution of Hedwigidium is documented and mapped. Literature records are verified for Europe (United Kingdom, Norway, France, Italy, and Spain), Africa (Cameroon, DR Congo, Malawi, Tanzania, Uganda, Zimbabwe, South Africa, Reunion Island, Kenya), and Southeast Asia (India, Sri Lanka, Indonesia). In the New World, Hedwigidium is confirmed for Mexico, Guatemala, El Salvador, Honduras, Costa Rica, Dominican Republic, and South America (Venezuela, Colombia, Ecuador, Peru, Bolivia, Chile, Argentina, and Brazil). Conclusions: The data and statistical analyses presented here refute the taxonomic conclusion proposing Hedwigidium is synonymous with Braunia. None of the Braunia species has a seta as short as that of Hedwigidium. Therefore, still surviving unrefuted is the alternative hypothesis that Hedwigidium is a separate genus. Taxonomic characters important in distinguishing this genus from other genera in the Hedwigiaceae are discussed.